THE IMPACT OF DIGITAL TRANSFORMATION IN IMPROVING THE BANK'S REPUTATION AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF IRAQI PRIVATE BANK EMPLOYEES - Wahab Mahdi Wahab; Hawraa Zaki Hameed (Scholars Digest Publishing, 2023)
Digital transformation techniques help transform the work that is done by traditional methods and tools into electronic work through the use of Internet and computer technology because of the role of these technologies in the speedy completion of work in addition to accuracy and efficiency in work and reduce effort and cost, and among the sectors that have adopted this technology in their work are The banking sector, due to its activities that require intelligence in dealing with customers in order to be able to attract and retain customers through banks providing services and exchanging information between them and customers quickly and with high accuracy, while ensuring the confidentiality and security of transmitted information. Therefore, this study aims to identify modern technology in financial transactions and to demonstrate the importance of adopting Iraqi private banks for digital operations such as electronic money transfer, electronic payment processes, financial settlements, as well as electronic clearing, and to demonstrate the impact of this on the reputation of banks through its reflection on the market value of the bank's share, the return of shareholders and the share The market that appears through the number of dealers with the bank, including depositors, borrowers, and investors, and do these banks have the appropriate environment for applying these technologies, the extent of public interaction with these technologies, and does he have confidence in dealing with them, and that the reason for selecting the sample for this study is the Iraqi private banks, with the aim of advancing the reality of Iraqi banks to keep pace with Technological developments in the world by distributing a questionnaire to a sample of academics and workers in the banking sector.
Keywords: digital transformation, strategic transformation, organizational reputation.